SQL: The Complete Reference - Weinberg Paul (Mc Graw Hill, 2009)
Get comprehensive coverage of every aspect of SQL from three leading industry experts. Revised with coverage of the latest RDBMS software versions, this one-stop guide explains how to build, populate, and administer high-performance databases and develop robust SQL-based applications.